Comics about the Covid-19 pandemic as scientific dissemination in the social networks of Casa da Descoberta (Research, Society and Development, 2022)
Objective: this paper aims to describe the use of comics on themes related to the Covid-19 pandemic, as a means of scientific dissemination on social networks, facebook and instagram, by Casa Descoberta (CD), a scientific dissemination center at the Fluminense Federal University. Methodology: initially a diagnostic questionnaire was elaborated to understand which themes related to Chemistry and Science with the Covid-19 pandemic, that the general public would be interested in knowing. The questionnaire was sent in september 2020 via googleform through the social network. Considering the responses of 51 people, 10 animated comics were created and published periodically on facebook and instagram of CD from November/2020 at mars/2021. The topics covered ranged from alcohol gel, cleaning materials, soap and sanitizers, about Coronavirus, tests for Covid-19, importance of vaccines, history of pandemics until types of vaccines. For the production of the comics, the storylines and scripts were first elaborated, until the final production using the Canva® application, always based on scientific information, which were referenced before the credits of the comics. Aiming to be an attractive and dynamic product and taking into account the characteristics of the means of communication, the comics were animated for facebook and in the form of a post for instagram containing about 10 frames. The characters used were the CD's mascots that dialogued with each other and directly with the audience. Results: through the number of likes, views and shares, in addition to public comments, the importance and interest of people in this type of approach and means of scientific dissemination was perceived. Conclusion: it was possible to observe that comics can be a playful and important instrument of scientific dissemination.